Design and Implementation of the Ulul Albab Teacher Training Program at Imtiaz Schools in Malaysia - Mohd Fakhruddin, Fathiyah; Salim, Siti Suria; Hassan, Siti Aishah; Suhid, Asmawati; Othman, Shamsudin (SCAD Independent, 2021)
Ulul Albab education is an education that offers in selected secondary schools in Malaysia. In the context of the teachers at the Ulul Albab schools, the in-service program is essential as the existing pre-service programs do not directly focus on the concept of Ulul Albab education. This qualitative study aims to examine the design and implementation of the Ulul Albab teacher training program at Imtiaz secondary schools. This qualitative study employed the case study method by interviewing six participants using a purposive sampling technique consisting of Ulul Albab program coordinators, Imtiaz secondary school principal, and four teachers at Imtiaz secondary schools who performed Ulul Albab programs. The findings showed that there are several designs of teacher training programs such as Quranic culture, explanation of school mission, benchmarking visits to excellent schools, and the emphasis on holistic education concept. The findings of the study also indicate that the implementation of teacher training programs should be carried out periodically, and consistently by the school and relevant departments. This study has important implications for professional development programs for Ulul Albab teachers during their services, especially on the aspects that have been highlighted in the study findings.